Instagram Activation as a part of University Public Relations Social Media Orchestration - Maya Amalia Oesman Palapah (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2020)
The dissemination of information is carried out in various ways, one of them through Instagram. An Instagram account should not only be a visual performance but also a place for interaction with the public. This research aims to identify a combination of various aspects carried out in the @universitasislambandung account so that it can become an attractive presentation to create an orchestration that is pleasing to the public. The method used in this research is qualitative research. Data collection techniques were carried out by interview, observation and literature study. The results of this research indicate the initial stages of identifying aspects of social media activation in the form of engagement mode on the @universitasislambandung Instagram account with its unique users. The uniqueness can be seen from the combination of the thematic agenda with Unisba's vision and mission which is manifested in publications and interactions in the chat column, in the form of comments and direct messages. This research also produced a number of recommendations to optimize the performance of this Instagram account as a representation of the institutions on syle and delivery mode by utilizing additional features available on Instagram.